Humidity controlling material development from diatomite, waste glass and cockle shell powder: an experimental study - Huong, Pei Zam; Zainal Abidin, Emilia; Karuppiah, Karmegam; Salit, Mohd Sapuan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Innovative ways of balancing indoor relative humidity without compensate for the optimal working environment is crucial as excessive dampness is a risk factor for health symptoms among people and deteriorate building performance. This study examines the potential of fabricating humidity controlling material by sintering a mixture of diatomite, waste glass and cockle shell powder. Moisture sorption isotherms, moisture buffer values, pore structure, surface morphology and flexural strength of the final products were determined. Methods: Mixture of diatomite, powdered waste glass and cockle shell powder is mixed at different ratio, pressed and sintered at 1100°C for 20 minutes. The final products were examined using nitrogen gas adsorption-desorption and scanning electron microscopy for mesoporous and morphology properties. The moisture adsorption-desorption performances of the samples were tested using desiccator method while the flexural strength is tested using universal testing machine. Results: The sintered products have specific surface area from 5.744 m2/g to 14.765 m2/g and have pore size from 39.5-67.7 nm. The best product, manufactured by mixing 60% diatomite, 30% waste glass and 10% cockle shell powder, showed a good moisture buffer value (MBV: 1.3 g/m2 %RH) and flexural strength of 8.23 ± 1.8 MPa satisfy the standard of those commercial porous ceramics. Conclusion: Usage of waste glass and cockle shell powder in development of humidity control material helped in the waste reduction. The humidity control material produced can regulate indoor humidity without additional energy consumption. The superior products show excellent characteristics and highly promising for various construction applications.